Effectiveness of interventions to increase physical activity in individuals with intellectual disabilities: a systematic review of randomised controlled trials. Issue 2 (8th November 2018) - Hassan, N. M.; Landorf, K. B.; Shields, N.; Munteanu, S. E.
Abstract: Background: People with intellectual disabilities (ID) often do not meet recommended guidelines for physical activity. The aim of this study was to systematically review available evidence that evaluated the effectiveness of interventions to increase physical activity in individuals with ID. Method: Five electronic databases (MEDLINE, CINAHL, EMBASE, SPORTDiscus and Cochrane Central Register of Controlled Trials) were searched from inception of the database to July 2017 to identify randomised controlled trials that evaluated the effectiveness of interventions to improve physical activity among people with ID. Trials were included if they measured at least one objective measure of physical activity. Quality appraisal was completed by two independent reviewers using the Cochrane Risk of Bias Tool. The magnitude of treatment effect was estimated for each intervention by calculating the standardised mean difference (SMD) and associated 95% confidence interval. Results: Nine randomised controlled trials (976 participants, 501 women, age range 9 months to 83 years) were included. Four trials evaluated unimodal interventions and five trials evaluated multimodal health promotion programmes based on using supportive environments to enable sustained behavioural changes in physical activity. None of the trials were rated as low risk of bias as all had at least one item on the Cochrane Risk of Bias Tool that was considered to be high risk. No trials were able to implement participant blinding. Three trials found statistically significant beneficial effects of interventions for increasing physical activity. Results showed that a 10‐week progressive resistance training programme led to maintenance of physical activity levels at 24 weeks in adolescents with Down syndrome (SMD 0.78, 95% CI 0.17 to 1.40). Additionally, a 12‐ to 16‐month multicomponent diet and physical activity programme produced improvement in physical activity at programme completion in adults with ID (reported effect size of 0.29). Finally, an 8‐month physical activity and fitness programme increased physical activity at 8 months in adults with ID (SMD 0.91, 95% CI 0.20 to 1.60). Findings regarding other interventions were inconclusive with small effects that were not statistically significant. Conclusions: There is inconsistent evidence of the effects of interventions for improving physical activity levels in individuals with ID. A progressive resistance training programme was found to maintain physical activity levels in adolescents with Down syndrome, while a multicomponent diet and physical activity programme and a physical activity and fitness programme were found to improve physical activity levels in adults with ID. Future trials using rigorous research designs are required to confirm these findings and establish whether other interventions designed to increase physical activity in people with ID are effective.